Pendampingan Pengembangan Model Bisnis Mahasiswa Dengan Business Model Canvas (BMC) - Erick Karunia; Nursia Nursia; Roni Padliansyah; Suryaningsih Suryaningsih; Deni Marsha; Nurul Hidayat; Nizhammuddin A.B; Syahran Syahran; Ahmad juliana; Sudarto Sudarto (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
This Community Service Program was carried out to enhance students’ abilities in designing and developing business models using the Business Model Canvas (BMC). The program was implemented through several stages, including the introduction of entrepreneurial concepts, training on the preparation of business models, intensive mentoring sessions, and final presentations of the developed business plans. The participants consisted of students who have an interest in entrepreneurship and were in the early stages of formulating their business ideas. Throughout the mentoring process, students were guided to identify customer segments, formulate value propositions, determine marketing channels and customer relationship strategies, and structure cost components and revenue streams. The results of the program indicate an improvement in students’ understanding and skills in applying the BMC framework in a comprehensive and practical manner. Students were able to organize their business ideas more systematically and became more prepared to proceed to market validation and initial implementation. This program contributes to strengthening the entrepreneurial mindset in higher education and supports the role of universities as facilitators in developing student-led business initiatives.